Profil Tingkat Kesegaran Jasmani Siswa Kelas IV dan V Sekolah Dasar Indonesia Kota Kinabalu Tahun Ajaran 2018/2019 - Ischaq, Maulana; Hanani, Endang Sri; Agus, Anugrah; Abdul Latip, Nur Nadzirah Binti (TEGAR: Journal of Teaching Physical Education in Elementary School, 2019)
The purpose of this study was to investigate  the physical fitness level profile of fourth grade and fifth elementary school students of SD SIKK (Kinablu City School Indonesia Sabah Malaysia) in the academic year 2018/2019. It’s used quantitative method. Data collection used the Asian Committee on the Standardization of Physical Test (ACSPFT) technique for under 12 years old. Data analysis used using descriptive percentages. The results showed that physical fitness profile of fourth grade  elementary school students were excellent 0%, good 7%, fair 46%, poor 20 36%, very poor 11%. The physical fitness profile of fifth grade  elementary school students were very good 4%, good category 20%, fair 47%, poor 22%, very poor category 7%. This reseach conclude that physical fitness condition of fourth grade and fifth elementary school students of SD SIKK was in fair category. AbstrakTujuan dalam penelitian ini adalah untuk mengetahui untuk profil tingkat kesegaran jasmani siswa kelas IV dan V SD SIKK (Sekolah Indonesia Kota Kinablu) Sabah Malaysia tahun ajaran 2018/2019. Metode penelitian ini adalah jenis Kuantitatif. Pengumpulan data menggunakan teknik survei tes Asia Commite on the Standardization of Physical Test (ACSPFT) untuk usia kurang dari 12 Tahun. Analisis data yang digunakan menggunakan deskriptif presentase. Hasil penelitian menunjukkan bahwa Profil Kesegaran Jasmani siswa kelas IV sebagai berikut, baik sekali 0%, kategori baik 7%, kategori cukup 46%, kategori kurang 36%, kategori kurang sekali 11%. Profil Kesegaran Jasmani siswa kelas V baik sekali 4%, kategori baik 20%, kategori cukup 47%, kategori kurang 22%, kategori kurang sekali 7%. Dari hasil penelitian menunjukan profil kesegaran jasmani siswa Kelas IV dan V SD SIKK Sabah Malaysia rata-rata dalam kategori cukup.